PRODUCTION OF 1,3-OXAZOLIDINE DERIVATIVE - NAKANO TATSUYA; ISHII YASUTAKA (2000)
PROBLEM TO BE SOLVED: To obtain the subject derivative useful for wide areas, from readily available stock materials by a simple method and in high yield, by reacting a specific imine derivative with a specific epoxy compound. SOLUTION: This derivative, shown by formula III, is obtained by reacting (A) an imine derivative shown by formula I [R1 and R2 are each H, a hydrocarbon or heterocyclic group, where R1 and R2 are bound to each other together with the adjacent carbon atom to form a ring; and R3 is H, a hydrocarbon, heterocyclic group, OH, substituted oxy or (substituted) amino], including not only imine compounds of a narrow sense but also those of a broad sense having a C=N bond, e.g. oxime (ether) and hydrazone derivatives, with (B) an epoxy compound shown by formula II [R4 to R7 are each H, a hydrocarbon or heterocyclic group, where R4 and R5, R6 and R7, and R4 and R6 are bound to each other together with the adjacent carbon atom or C-C bond to form a ring], in the presence of, as required, a catalyst of metallic compound, the metal preferably belonging to the group 3 in the periodic table.